Temporal evolution of the lower hybrid cavities in the ionosphere plasma due to turbulent diffusion - Azarenkov, N.A.; Chibisov, D.V.; Kovalenko, N.I.; Maslennikov, D.I. (Вопросы атомной науки и техники, 2019)
The problem of evolution and disappearance of the lower hybrid cavities that are observed in the plasma of the Earth’s ionosphere is solved. It is assumed that the destruction of the cavity is caused by turbulent diffusion of plasma, which arises due to the drift instability of radially inhomogeneous plasma. The initial plasma density distribution on the radius in the cavity is considered to be the inverse Gaussian distribution. A solution of the diffusion equation is obtained, which at any time determines the radial dependence of the plasma density in the cavity. In the asymptotic limit t →∞ the plasma density in the cavity becomes equal to the density of the surrounding plasma. Вирішується проблема еволюції і зникнення нижньогібридних порожнин, які спостерігаються в плазмі іоносфери Землі. Передбачається, що руйнування порожнини викликане турбулентною дифузією плазми, яка виникає через дрейфову нестійкість радіально-неоднорідної плазми. В якості початкового радіального розподілу щільності плазми в порожнині розглядається зворотній розподіл Гаусcа. Отримано рішення рівняння дифузії, яке в будь-який момент часу визначає залежність від радіуса щільності плазми в порожнині. Показано, що в асимптотичній границі t → ∞ щільність плазми в порожнині стає рівною щільності навколишньої плазми. Решается проблема эволюции и исчезновения нижнегибридных полостей, наблюдаемых в плазме ионосферы Земли. Предполагается, что разрушение полости вызвано турбулентной диффузией плазмы, которая возникает из-за дрейфовой неустойчивости радиально-неоднородной плазмы. В качестве начального радиального распределения плотности плазмы в полости рассматривается обратное распределение Гаусса. Получено решение уравнения диффузии, которое в любой момент времени определяет зависимость от радиуса плотности плазмы в полости. Показано, что в асимптотическом пределе t → ∞ плотность плазмы в полости становится равной плотности окружающей плазмы.